2010
DOI: 10.1590/s0102-05362010000100004
|View full text |Cite
|
Sign up to set email alerts
|

Water use and onion crop production in no-tillage and conventional cropping systems

Abstract: The objective of the present study was to evaluate the effects of crop residue covers (0.0; 4.5; 9.0; 13.5 t ha-1 millet dry matter) on water use and production of onion cultivated in no-tillage planting system (NT) as compared to conventional tillage system (CT). The study was carried out at Embrapa Hortaliças, Brazil, under the typical Savanna biome. Irrigations were performed using a sprinkle irrigation system when soil-water tension reached between 25 and 30 kPa. The experimental design was randomized bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…However, soil moisture content was statistically significant in soil mulched with sawdust at both depths at the fourth sampling date. This result is in agreement with Marouelli et al, 2010 who observed that reduced moisture loss was due to the covered soil surface.…”
Section: Soil Moisture Contentsupporting
confidence: 93%
“…However, soil moisture content was statistically significant in soil mulched with sawdust at both depths at the fourth sampling date. This result is in agreement with Marouelli et al, 2010 who observed that reduced moisture loss was due to the covered soil surface.…”
Section: Soil Moisture Contentsupporting
confidence: 93%
“…Because of the soil conservation importance for onion growers some experiments are being conducted using different cropping systems. The use of cover crop residues increased water use and onion yields cultivated in NTS in comparison with CTS in Brazilian cerrado condition (MAROUELLI et al, 2010). In an agro-ecological NTS in Ituporanga's region the addition of cover crop residues in no-tillage contributed to the growth and onion yields over the years (SOUZA et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Onion grown under CA reduced 30% of the irrigation water for the first 30 days of the cycle and 19% along the cultivation compared to conventional tillage (MAROUELLI et al, 2010). In study of tomato crop, Marouelli et al (2006) reported an increase of 23% in water use efficiency under no-tillage, when compared to conventional tillage.…”
Section: Soil Water Contentmentioning
confidence: 94%
“…Using cover crops in crop rotation and straw production for no-tillage improves environmental conditions by increasing soil fertility through nutrient recycling and increase of organic matter (BENINCASA et al 2017;HOYT et al 1994). As a consequence, it increases soil water content (NOVELLI et al 2017;MITCHELL et al 2012;MAROUELLI et al 2010), the stability of soil aggregates (WILLIAMS & WEIL, 2004;ROSOLEM et al 2002), the organic matter and nutrients (NYAMBO et al, 2020;BRANCO et al 2017), the microbiological activity (DUDA et al 2003;HOLAND, 2004) and, finally, the crop yield (AHMADIANI et al 2016;MELO et al 2010;MAROUELLI et al 2006).…”
Section: Introductionmentioning
confidence: 99%